Excellent response to combined radioiodine and enoxaparin in the setting of tumor venous thrombosis from differentiated thyroid carcinoma involving internal jugular and subclavian veins. (December 2013) - Basu, Sandip; Pantvaidya, Gouri; Malvadkar, Sharad
A striking clinical, radiological and tumor marker response obtained with a combined approach of radioiodine (I-131; single fraction) coupled with subcutaneous enoxaparin (a low-molecular-weight heparin) in the setting of differentiated thyroid carcinoma with jugular vein tumor thrombosis and metastatic pulmonary disease is described in this article. Pulmonary metastases, a frequent accompaniment in this group of patients, also demonstrated remarkable response with a single fraction of I-131. The proposed approach of combining targeted I-131 therapy with the antithrombotic effect of low-molecular-weight heparin in patients with thyroid cancer with documented tumor venous thrombosis is likely to produce a synergistic effect, with a dramatic clinical response that requires a minimal I-131 dose. The noninvasive nature and ease of the approach, which has an impressive response and findings, calls for administering this therapeutic option more in such patients in the future. This could lead to the development of an effective treatment strategy in these patients based upon generated evidence.